Natural radionuclides in lichens, mosses and ferns in a thermal power plant and in an adjacent coal mine area in southern Brazil - Galhardi, Juliana Aparecida [UNESP]; García-Tenorio, Rafael; Díaz Francés, Inmaculada; Bonotto, Daniel Marcos [UNESP]; Marcelli, Marcelo Pinto (Elsevier, 2017)
The radio-elements 234U, 235U, 238U, 230Th, 232Th and 210Po were characterized in lichens, mosses and ferns species sampled in an adjacent coal mine area at Figueira City, Paraná State, Brazil, due to their importance for the assessment of human exposure related to the natural radioactivity. The coal is geologically associated with a uranium deposit and has been used as a fossil fuel in a thermal power plant in the city. Samples were initially prepared at LABIDRO (Isotopes and Hydrochemistry Laboratory), UNESP, Rio Claro (SP), Brazil. Then, alpha-spectrometry after several radiochemical steps was used at the Applied Nuclear Physics Laboratories, University of Seville, Seville, Spain, for measuring the activity concentration of the radionuclides. It was 210Po the radionuclide that most bio-accumulates in the organisms, reaching the highest levels in mosses. The ferns species were less sensitive as bio-monitor than the mosses and lichens, considering polonium in relation to other radionuclides. Fruticose lichens exhibited lower polonium content than the foliose lichens sampled in the same site. Besides biological features, environmental characteristics also modify the radio-elements absorption by lichens and mosses like the type of vegetation covering these organisms, their substrate, the prevailing wind direction, elevation and climatic conditions. Only 210Po and 238U correlated in ferns and in soil and rock materials, being particulate emissions from the coal-fired power plant the most probable U-source in the region. Thus, the biomonitors used were able to detect atmospheric contamination by the radionuclides monitored.
Keywords: Bio-monitoring; Coal-industry; Polonium; Southern Brazil; Thorium; Uranium